2020
DOI: 10.1515/nleng-2020-0010
|View full text |Cite
|
Sign up to set email alerts
|

MHD natural convection flow of Casson fluid in an annular microchannel containing porous medium with heat generation/absorption

Abstract: AbstractThis study has been conducted to focus on natural convection flow of Casson fluid through an annular microchannel formed by two cylinders in the presence of magnetic field. The process of heat generation/absorption is taken into consideration. Combined effects of various parameters such as porous medium, velocity slip and temperature jump are considered. Solution of the present mathematical model is obtained numerically using fourth-fifth order Runge-Kutta-Fehlberg meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…Khan et al [15] investigate the three-dimensional axisymmetric steady ow of micropolar uid over a rotating disk in a slip-ow regime. Zhang et al [16] studied the blood ow's entropy analysis through an anisotropically tapered artery under the suspension of magnetic Zinc-oxide nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…Khan et al [15] investigate the three-dimensional axisymmetric steady ow of micropolar uid over a rotating disk in a slip-ow regime. Zhang et al [16] studied the blood ow's entropy analysis through an anisotropically tapered artery under the suspension of magnetic Zinc-oxide nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…Idowu et al (2020a) presented the analysis of Casson fluid flowing through the annular channel. Second law analysis with Casson rheology investigation in annular microchannel justified by Gireesha and Roja (2020) and Gireesha and Sindhu (2020b). Thriveni Likewise, appreciable progress has been made in studies related to the MHD phenomenon as a result of prompt importance in electrolytes, liquid metal, and ionized gases.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a series of investigations of convective flow in a vertical annular porous medium have been carried out. Jha et al, 6 Oni and Jha, 7 Jha et al, 8 Yusuf, 9 and Jah and Yusuf 10 analyzed the transient free convective flow through the porous material; Isa et al 11 observed the steady‐state flow regime and time‐periodic boundary conditions through a vertical microcircular duct; and recently, Gireesha and Sindhu 12 performed the analysis on the heat absorption/generation of a Casson fluid flow through the annular microchannel. They established that a higher magnitude of Casson and Hartmann's number decelerates the fluid momentum, and that the heat‐generating parameter predicts the skin friction positively.…”
Section: Introductionmentioning
confidence: 99%